Geospatial technique for the delineation of groundwater potential zones using multi-criteria-based AHP and MIF methods - Amit Prakash Multaniya; Manish Kumar Sinha; Kamal Kishor Sahu; Shubham (Water Supply, 2024)
In the recent past, the growing climate change and transformation of the green cover into urban areas have posed a threat to natural water supply, which will have a direct impact on water demand for emerging cities such as Nava Raipur. As a result, the increasing demand coupled with the reduced availability of surface water prompts scientific investigation into groundwater availability and its sustainable management as an alternative. The study attempted to determine groundwater potential zones using the analytic hierarchy process (AHP) and multi-influencing factor (MIF) techniques. Twelve contextually significant regulating environmental factors were selected, and their significance and influences on decision-making approaches models have been attempted to determine through the sensitivity analysis. The final GWPZ map obtained, from a combination of thematic layers, was verified using the receiver operating curve (ROC) and the area under curve (AUC) with discharge (yield) records taken from 21 bore wells. According to the ROC curve's AUC estimation, MIF can explain 82.9% of the actual groundwater situation in the region, and for AHP, an AUC value of 0.751 is relatively low. This indicates that the MIF model is the most appropriate to accurately define potential groundwater zones for emerging cities like Nava Raipur. HIGHLIGHTS AHP and MIF methods of the MCDA approach have been applied for groundwater potential zone mapping.; The GWPZ maps are validated with field observed yield data of 21 wells.; The conventional validation approach has been changed using ROC and AUC approaches.; To understand the weightage or sensitivity of each thematic layer, sensitivity analysis was performed.;